DAMPAK TEKNOLOGI DIGITAL PADA PENDIDIKAN TINGGI DI INDONESIA - H. Masri, Zainal Arifin (Jurnal Edukasi Ekonomi, 2025)
This study explores the impact of digital technology on higher education in Indonesia by examining its contributions, challenges, and implications for teaching and learning processes. Using a qualitative descriptive–exploratory design, the research synthesizes findings from literature reviews, interviews, classroom observations, and document analysis. The results show that digital technology significantly expands educational access, particularly for students in remote regions, through online learning platforms, Learning Management Systems (LMS), and AI-based learning tools. Digitalization also enhances pedagogical innovation by enabling interactive, flexible, and personalized learning experiences. However, implementation remains uneven due to infrastructural disparities, limited digital competence among educators, and variations in school readiness across regions. The study further identifies emerging social and ethical concerns, including reduced face-to-face interaction, digital dependency, and data-privacy vulnerabilities in online learning platforms. Government initiatives—such as Merdeka Belajar, Palapa Ring, and the provision of “belajar.id” accounts—have contributed to strengthening the digital education ecosystem, yet gaps persist, especially in 3T areas. Overall, the study concludes that maximizing the benefits of digital technology requires comprehensive policies, strengthened infrastructure, continuous digital-literacy training for educators and students, and improved data-protection standards. This research contributes to the literature by offering a holistic understanding of the opportunities and barriers of digital transformation in Indonesian education and provides practical recommendations for ensuring inclusive, sustainable, and equitable implementation.